Identification of the orthotropic diffusion properties of RTM textile composites for aircraft applications. (March 2016) - Beringhier, M.; Simar, A.; Gigliotti, M.; Grandidier, J.C.; Ammar-Khodja, I.
Abstract: The paper focuses on a novel strategy for the rapid identification of the orthotropic diffusion properties of RTM textile composite materials for aircraft applications. The method consists in performing gravimetric tests on composite samples and then employing the Proper Generalised Decomposition method for the identification of a 3D orthotropic Fickian model. The method consists in calculating once and for all the solution for a given range of the diffusion parameters and then in particularising such a solution in accord with the experimental results by an optimisation procedure. Analysis and discussion of results show that the identification can be performed successfully.